Experiences of oral pre‐exposure prophylaxis use among heterosexual men accessing sexual and reproductive health services in South Africa: a qualitative study - Fatima Abegail Cholo; Siphokazi Dada; Catherine Elizabeth Martin; Saiqa Mullick (Journal of the International AIDS Society, 2024)
Abstract Introduction South African men face a substantial burden of HIV and are less likely to test for HIV and initiate antiretroviral therapy if tested positive and more likely to die from AIDS‐related causes than women. In addition to condoms and circumcision, guidelines provide for the use of daily oral pre‐exposure prophylaxis (PrEP) as an HIV prevention intervention for any men who recognize their need and request PrEP. However, heterosexual men have not been a focus of PrEP programmes, and since its introduction, there is limited literature on PrEP use among men in South Africa. This study explores the experiences, motivators and barriers to oral PrEP use among heterosexual men accessing primary healthcare services in South Africa. Methods This study forms part of a mixed‐methods implementation science study aimed at generating evidence for oral PrEP introduction and conducted in primary healthcare clinics in South Africa since 2018. Men aged ≥15 years who initiated oral PrEP and enrolled in a parent cohort study were purposefully invited to participate in an in‐depth interview (IDI). Between March 2020 and May 2022, 30 men participated in IDIs exploring their motivators for PrEP use, and experiences with accessing health services. Interviews were audio recorded, transcribed and analysed thematically. Results The final analysis included 28 heterosexual men (18–56 years old). Motivations to initiate PrEP included fear of acquiring HIV, self‐perceived vulnerability to HIV and mistrust in relationships; health systems factors which motivated PrEP use included the influence of healthcare providers, educational materials and mobile services. Perceived reduction in HIV vulnerability and changing proximity to partners were reasons for PrEP discontinuation. Side effects, daily‐pill burden and stigma were noted as challenges to PrEP use. Health system barriers to PrEP use included limited PrEP availability, school and work demands, and inconsistent mobile clinic schedules. Conclusions Our study reports on the experiences of heterosexual men accessing oral PrEP in real‐world settings and contributes to the limited literature among this population. We highlight multiple levels which could be strengthened to improve men's PrEP use, including individual support, education among partners and communities, and addressing health system barriers to access.